Processo adaptativo de idosos em tratamento hemodialítico: uma análise à luz do modelo de Roy - Bastos, Rosângela Alves Almeida (2013)
Population aging is a meaningful growing phenomenon, what makes the individual more vulnerable to acute non transmitted diseases such as chronic renal disease that predispose elderly to the need of hemodialysis to survive, demanding a constant adaptive process due to the modifications provoked by such illness and its therapeutics. Despite this, there are few studies that approach the phenomenon. Considering what has been exposed, the present study aims analyzing, in the light of Roy s model, the elderly adaptive process when submitting to hemodialysis. This is an exploratory study involving fifteen elderly people suffering chronic renal disease treated at a specialized Clinic in the city of João Pessoa, Paraíba. The data was collected in the period of January to April of 2012, by recorded interviews having a semi-structured script. The analysis of the corpus was carried by a qualitative approach using the content analysis technique and the guiding principle were four pre-established thematic categories corresponding to the adaptive modes proposed by Roy: physiologic, self-concept, function in the real life and interdependence. In relation to the physiological mode were identified inefficient responses related to oxygen components, nutrition, elimination, fluids, electrolytes, endocrine function, activity and repose/rest, protection and senses. Regarding the relative category to the self-concept mode, the elderly showed inefficient behavior related to the physiological self such as the feeling of despair, sadness and death, embarrassment and stigma related to the modification in their body image provoked by the both the illness and the treatment. As to the personal self, some elderly presented an efficient coping of the illness and therapeutics, what favored a positive adaptive process manifested by feelings of hope, cure, dreams, desire and faith in God. Concerning the representative category of the function mode of real life/interdependence, the elderly showed inefficient behavior such as feeling of impotence due to the loss of their social role, dissatisfaction, changes in the social and family living, and bonds of friendships. In this category were also observed positive affective behavior to face the illness situation, such as the support from their family, friends and the Health professionals that promoted improvement in the adaptive process of the elderly. The results of the present study allowed us to infer that the elderly undergoing hemodialysis present difficulties to adapt to the illness and the treatment. In view of this finding, the present research can give support to the health staff, in especial to the Nursing, to the planning of interventions that can contribute to the help the elderly to cope with the difficulties provoked by the treatment of the analyzed phenomenon, what implies in improvement in their lives.